Avaliação ambiental e forma de transporte de agrotóxicos organoclorados no Rio Jaguaribe - CE - Oliveira, André Henrique Barbosa de (2012)
Organochlorine pesticides (OCs) have been extensive ly used in the post-war II, with its trade and distribution restricted in several countries in the mid-80s, including Brazil, because of their toxicological effects. The present study aims at evaluating the environmental dynamics of OCs pesticides, as well as its impact on sub-basin of low Jaguaribe - CE. For this run were the specific objectives: Development of protocol analysis of pesticides in environmental matrix soli d (sediment); Assessment of COs distribution of pesticides in the sediment of the s ub-basin of low Jaguaribe-CE; Evaluation of parameters governing the deposition of pesticide COs and an assessment of ecological risk. The used chromatographic techniques (GC-MS and GC-ECD) showed satisfactory results with respect to analyti cal validation parameters. The compounds detected in the study were: γ-HCH (lindane), hexachlorobenzene, heptachlor, o,p-DDE, p, p- DDD, o, p-DDT and methoxychlor. The compounds α-BHC, β-BHC and endosulfan were below the LD and LQ technique. Levels of COs ranged from not detected to 14,84 ng/g in fluvial environment domain. In the estuary, the change was not detected to 51,89 ng/g. The highest and lowest concentrations were respectively heptachlor (51,89 ng/g) in the estuary and lindane (γ-HCH) (3,15 ng/g) in the river portion. In sediment samples from estuarine zone can be observed the highest concentrations of COs in relation to river area. Similar levels were found in coastal regions of China (0,1-11,1 ng/g.) In relation to the area of study (0,41-3,45 ng/g). Agricultural activities, programs eradication of disease vectors, release of industrial wastes and their physico-chemical nature are cited as the main causes for the presence of these COs in the environment. There was a greater tendency to deposition of γ-HCH (lindane), heptachlor and p,p-DDT associated with fines content (clay + silt) and humic fractions in predominantly fluvial environment. Under estuarine area, pesticides γ-HCH (lindane), heptachlor showed the same trend associating predominantly fine fraction. The levels of the pesticide p,p-DDD (2,42 ng/g) were detected in sediment samples from the river and estuarine low Jaguaribe showed a high potential ecological risk to biota, which may act as causative agent of harmful effects to the ecosystem estuarine analyzed.